STRUCTURAL AND PHASE COMPOSITION OF STEELS R6M5 AND 40H AFTER JOINT HEAT TREATMENT - A. M. Milyukova (Литьë и металлургия)
The paper discusses special features of heat treatment of axial (end) cutting tool bimetallic billets made using the resource-saving technology with the aid of simultaneous hot plastic deforming through a forming die. The microstructure and hardness of 40X and P6M5 steels have been investigated after subjecting them to various conditions of heat treatment.